ORGANIZATIONAL CULTURE, ORGANIZATIONAL CLIMATE AND EMPLOYEE ACHIEVEMENT AT SENIOR HIGH SCHOOL IN MINAHASA - Sondakh, Octavianie B.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2020)
The development of the world of education is still running relatively slowly in Indonesia, there are still many obstacles and challenges for teaching staff or in this case teachers, have difficulty in developing their potential. Because lack of support to increase their potential and it has an effect on their achievement, to see how the circumstances affect teacher performance and motivation is interesting topic. In this research, is used qualitative analysis, in which the method is to explain and describe about the employee achievement based on their surrounding which is organizational culture, and organizational climate. In this study obtained conclusion, that employee achievement is based on the environment around the school, such as facilities provided by the school, affordable access to schools and the cooperation formed within the school environment are some of the things that have an influence on the level of employee achievement. Collaboration between fellow teachers needs to be further improved in order to achieve the common goal of improving school quality.Â Keywords: organizational culture, organizational climate, employee achievement